Особенности выращивания монокристаллов алмаза в системах на основе магния при температуре до 2000 °С - Коваленко, Т.В.; Ивахненко, С.А.; Белявина, Н.Н.; Заневский, О.А.; Лысаковский, В.В.; Серга, М.А. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2010)
The results of researches on growing of diamond single crystals in Mg–based growth systems
by a temperature gradient method at a variation of structure of solvent are presented. It is
proposed to isolate the growing volume of heating system to prevent pressure loss occurring in the
interaction of alloy-solvent with a graphite heater.